364 PEDIATRIC ASTHMA PREVALENCE AND CARE AMONG NATIVE AMERICAN YOUTH IN SOUTHEASTERN MONTANA. Issue 1 (1st January 2007) - Roberts, M.; Mark, D.
Abstract : Objective: To determine the period prevalence of asthma in youth accessing care at the Crow Service Unit in southeastern Montana during the years 1995-2005 and to evaluate adherence to national care guidelines. Setting: The Crow Service Unit, an Indian Health Service area that includes one hospital and two satellite clinics and serves a user population of 11, 400, approximately 5, 200 of whom are less than 21 years old. Methods: Retrospective electronic and manual chart review to identify pediatric patients (age less than 21 years old) with a diagnosis of asthma (ICD 493) who had at least one clinic visit during the given calendar year. Care given to pediatric patients during 2005 was evaluated by examining six discrete variables from the National Asthma Education and Prevention Program (NAEPP) guidelines. Results: The prevalence rate for pediatric asthma from 1995 to 2005 was 8.3%. The period prevalence ranged from 6.94 to 10.38% (see Figure ). Of the pediatric patients with asthma in 2005 ( N = 454), assessment to describe the severity of the patient's condition was performed in 29.7% ( n = 135) of cases; spirometry was performed in 7.9% ( n = 36) of cases; a written self-management plan was given or updated in 53.5% ( n = 243) of cases; patient's metered dose inhaler or nebulizer technique was assessed in 5.3% ( n = 24) of cases; and a follow-up plan was generated in 56.2% ( n = 255) of cases. Of the pediatric patients over age 5 years who had documented persistent asthma in 2005 ( n = 14), 71% ( n = 10) were treated with inhaled corticosteroids. Conclusion: Although the prevalence rate of asthma among Native American youth at the Crow Service Unit is similar to the general US pediatric population rate for all races in 2001 (8.7%), adherence to national standards of asthma care is suboptimal.